Citing medicine: the NLM style guide for authors, editors, and publishers (ukrainian translation) - Patrias, K.; Wendling, D. (Морфологія / Morphologia / Morfologìâ, 2018)
Citing medicine: the NLM style guide for authors, editors, and publishers (ukrainian translation)